Effects of anomalous cosmic rays on the solar wind events in the outer heliosphere - Zhou, Yucheng; Guo, Xiaocheng; Wang, Chi (Frontiers in Astronomy and Space Sciences, 2024)
Anomalous cosmic-rays(ACRs) are thought to be originated from the acceleration of pickup ions(PUIs) at the termination shock or interplanetary shocks, and play important role for the plasma dynamics in the outer heliosphere. Due to limited observation, the effects of ACRs on the solar wind events is not well known. Under the approximation of spherical symmetry, we have developed a three-component magneto-hydrodynamic(MHD) numerical model that contains solar wind plasma, interstellar neutral atoms and ACRs, to investigate the evolution of the solar wind within a heliocentric distance from 1 to 150 astronomical units(AU). We use the solar wind observations from the OMNI database with the time from 2010.5 to 2016.0 (decimal years) at the inner boundary, and the effect of ACRs on the propagation of the solar wind events are compared with the observations from the spacecrafts of New Horizons, Voyager 1 and 2. The results show that ACRs may decrease the speed of the solar wind shocks to some extent, and the effect is positively correlated with the diffusion coefficient; a larger diffusion coefficient leads to a more pronounced effect. Moreover, the ACRs has a dissipation effect on the shock-like solar wind structures, and may play important roles on the dynamics of solar wind in the outer heliosphere.